EFFECT OF BIOSURFACTANT PRODUCED BY BACILLUS IN OILY WASTEWATER DEGRADATION - Sri Kadarwati; Leni Herlina (Scientific Contributions Oil and Gas, 2008)
Liquid waste from oil industry activities has potential cause environmental pollution. These liquid wastes, containing hydrocarbon and heavy metals, are mostly toxic. Therefore, biotechnology by means of biological treatment can be applied for decomposing the toxic liquid wastes. The biosurfactant production from some microorganisms can support hydrocarbon degradation. The objective of this study is to examine the crude biosurfactant that is extracted from the selected Bacillus which was precipitated by using methanol on acid moiety. The crude biosurfactant extract were tested to support hydrocarbon degradation. Three species of Bacillus used in this experiment were compared based on their respective biosurfactant production. The results showed that the percentage of hydrocarbon degradation on liquid waste from refinery by the three Bacillus species were 90.23% (Bacillus subtilis), 88.72% (Bacillus licheniformis), and 73.43% (Bacillus laterosporus). The concentration of remaining oil after 28 days was 20.44 mg/L, 23.38 mg/L, and 54.87 mg/L, respectively. The decrease of COD were 84.90%, 84.04%, and 80.68%, respectively, and the COD value after 28 days treatment were 165 mg/L, 174 mg/L, and 211 mg/L.